(untitled) (Analysis in Theory and Applications, 2017)
This article is concerned with a system of semilinear parabolic equations with no-flux boundary condition in a mutualistic ecological model. Stability result of the equilibrium about relevant ODE problem is proved by discussing its Jacobian matrix, we give two priori estimates and prove that the model is permanent when ε_1+ε_2 eq 0. Moreover, sufficient conditions for the global asymptotical stability of the unique positive equilibrium of the model are obtained. Nonexistence of nonconstant positive steady states of the model is also given. When ε_1+ε_2 = 0, grow up property is derived if the geometric mean of the interaction coefficients is greater than 1 (α_1α_2 >1), while if the geometric mean of the interaction coefficients is less than 1 (α_1α_2